Experimental and numerical study on the indenting, buckling and piercing of aluminum beverage cans - Kh'ng, Jing Hui. (2013)
This study aims to investigate the factors that affect the strength and integrity of the aluminium cans. Specifically, the resilience of the aluminium cans to external damages under different conditions.